Menakar Hermeneutika Umar - Muhamad Zulfar Rohman (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2019)
Although not including in al-sabiqun al-awwalun, Umar was a shahaba of the Prophet who was very famous. During the time of jahiliyyah he was a person who really hated Islam, but when he converted to Islam and became a caliph he succeeded in making Islam spread to various regions. He is a person who organizes government administration so that Islam becomes a real country. In relation to the Qur’an he became a phenomenal person because his words seemed to precede the revealed verses of the Qur’an. The model of his understanding of the Qur’an in order to establish a policy is also interesting because it seems that he rejects the literal meaning of the Qur’an. This research aims to investigate and explain how Umar’s hermeneutics is working. The result was: first, the text in Umar’s hermeneutics was highly upheld. Second, Umar in understanding the Qur’an gives great attention to the context. Third, Umar was very progressive in carrying out ijtihad to achieve maslahat. Then also analyzed the applicative examples of Umar’s hermeneutics in the three cases: hadd cut off hands, giving zakat to muallafatu qulubuhum, and the division of ghanimah.